TINGKAT PENGETAHUAN TENTANG PENTINGNYAMENGKONSUMSI AIR M INERAL PADA SISWA KELAS IVDI SD NEGERI KEPUTRAN A YOGYAKARTA - Indah Prasetyowati Tri Purnama Sari (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbtractThe background of this study was because of many students of SD Negeri Keputran A in Yogyakarta at rest andafter exercise to consume a variety of instant drink and a variety of ice. The purpose of study was to determine theextent of knowledge about the importance of consuming mineral water on the fourth grade students in SD NegeriKeputran A Yogyakarta. This study is a descriptive study with approach kuantitaf. The method was a survey method. The study population was all students in the class IVA, IVB, and IVC SD Negeri Keputran A Yogyakarta in2013/2014 totaled 90 students. Samples were taken by using a total sampling. The instrument used of this studywas a knowledge test. Analysis using quantitative descriptive analysis presented in the form of a percentage. Theresults of this study indicate that the level of knowledge about the importance of drinking water consumed in the fourthgrade students in the Elementary School Keputran A Yogyakarta on the analysis of data for 59 students (65.56%)in the good category, 30 students of (33.33%) in the category quite well, as much as 1 students by (1.11%) in theunfavorable category, and no one category are not good (0%).Keywords: level of knowledge, mineral water consumtio, students grade 4, elementary schoolAbstrakPenelitian ini dilatarbelakangi oleh banyaknya siswa di Sekolah Dasar Negeri Keputran A Yogyakartapada saat istirahat dan setelah berolahraga mengkonsumsi berbagai minuman instan serta berbagai macames. Penelitian ini bertujuan untuk mengukur tingkat pengetahuan tentang pentingnya mengkonsumsi airmineral pada siswa kelas IV di Sekolah Dasar Negeri Keputran A Yogyakarta. Penelitian ini m e rupakanpenelitian deskriptif dengan metode survei. Populasi dalam penelitian ini adalah seluruh siswa kelas IV A,IV B, dan IV C SD Negeri Keputran A Yogyakarta pada tahun pelajaran 2013/2014 berjumlah 90 siswa.Sampel dalam penelitian ini diambil dengan menggunakan total sampling. Instrumen yang digunakan dalampenelitian ini berupa tes pengetahuan. Teknik analisis data menggunakan analisis deskriptif kuantitatifyang disajikan dalam bentuk persentase. Hasil penelitian ini menunjukkan bahwa tingkat pengetahuan tentangpentingnya mengkonsumsi air minum pada siswa kelas IV di SD Negeri Keputran A Y ogyakarta pada hasilanalisis data 59 siswa (65,56%) dalam kategori baik, 30 siswa (33,33%) dalam kategori cukup baik,sebanyak 1 siswa (1,11 %) dalam kategori kurang baik, dan tidak ada dalarn kategori tidak baik (0%).Kata Kunci: tingkat pengetahuan, konsumsi air mineral, siswa kelas 4, sekolah dasar.